Pemaknaan Potensi Lokal di Desa Wisata Rawabogo Kabupaten Bandung - Alma Verdiana (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. The tourism potential of Rawabogo Village became one of the urgencies after the establishment of the tourism village title in the village. Rawabogo Village, which is located in Ciwidey District, has been designated as a tourism village since 2011 with the potential for the Gunung Nagara Padang Site. However, until now this potential has not shown significant development. Rawabogo Tourism Village needs to explore the meaning of this phenomenon in order to know the real local potential. Based on this phenomenon, the method needed in addition to the instrumental concept (disstantiation) is also required for its meaning (appropriation). This research method uses a symbolic hermeneutic approach (Paul Ricoeur) which offers a new paradigm in the field of tourism village planning. This approach describes the meaning by combining